The Effectiveness of Salaman Application-Based Service Innovations for Homeless Beggars in Bandung City - Gaston Otto Malindir; Dede Sri Kartini; Rahman Mulyawan (UIN Sunan Gunung Djati, 2022)
As a form of service innovation, the Bandung City Population and Civil Registration Service applies Salaman application-based services. The word Salaman itself is an abbreviation of the word finished in hand. In practice, the Salaman application-based service implemented by the Department of Population and Civil Registration throughout 2019-2021 raises its own problems, especially for certain groups, such as homeless people, beggars, and other marginal groups in the city of Bandung. The purpose of this study was to analyze and describe the effectiveness of the service innovation of the Population and Civil Registration Service based on the Salaman application for the homeless and beggar groups. This research uses a descriptive method with a qualitative approach. Data collection techniques are carried out through interviews, observation and documentation, and data analysis techniques are carried out by data reduction, data display and drawing conclusions. The results of this study indicate that of the seven indicators used to measure the effectiveness of service innovations implemented by the Department of Population and Civil Registration of Bandung City, six of them showed poor results associated with groups of homeless people and beggars in the city of Bandung. The six indicators include clarity of purpose, clarity of strategy, process of policy analysis and formulation, careful planning, programming, and effective and efficient implementation. So overall it can be concluded that the Salaman application-based service innovation has not been effective in its application, especially if it is associated with groups of homeless people and beggars in the city of Bandung.